A complete route for biodegradation of potentially carcinogenic cyanotoxin microcystin-LR in a novel indigenous bacterium. (1st May 2020) - Yang, Fei; Huang, Feiyu; Feng, Hai; Wei, Jia; Massey, Isaac Yaw; Liang, Geyu; Zhang, Fang; Yin, Lihong; Kacew, Sam; Zhang, Xian; Pu, Yuepu
Abstract: Microcystin-leucine-arginine (MC-LR), a cyclic potentially carcinogenic hepatotoxin, occurs frequently in aquatic habitats worldwide and seriously threatens ecosystem and public health. Limited effectiveness of physicochemical treatments to remove MC-LR from drinking water has led to a search for alternative cost-effective and environment friendly biodegradation strategies. Obtaining MC-degrading bacteria and understanding their MC-degrading mechanisms are outstanding challenges. Here, a novel indigenous bacterium named Sphingopyxis sp. YF1 with a high efficient capacity for MC-degradation was successfully isolated from eutrophic Lake Taihu. Through integrating mass spectrometer and multi-omics analyses accompanied by functional verification of certain genes and proteins, a complete MC-degradation pathway was firstly identified, in which MC-LR was sequentially degraded into linearized MC-LR, tetrapeptide, Adda, phenylacetic acid, and finally potential product CO2 . Some specific proteins such as microcystinase, linearized-microcystinase, tetrapeptidease and PAAase responsible for this pathway were identified. This study pioneeringly demonstrated that MC-LR can be completely degraded through natural remediation processes and revealed a significant potential for MC-LR biodegradation in both natural environment and engineered systems. Graphical abstract: Image 1 Highlights: New MC-degrading genes and products were explored through a multi-omic approach. A complete MC degradation pathway was identified. A novel bacterium with high MC-degrading rate was isolated from Lake Taihu. Proteomics data of MC-degrading bacteria were obtained for the first time. A series of key enzymes responsible for detoxifying MC-LR were identified.